Fire, tractors, and health in the amazon: a cost-benefit analysis of fire policy - Morello, T; Martino, S; Duarte, AF; Anderson, L; Davis, KJ; Silva, S; Bateman, IJ (University of Wisconsin Press, 2019)
Pollution from agricultural fires is a global health issue that is particularly challenging where smallholders depend on burnings for subsistence. In Acre state, Western Amazon, a partial ban on fire, enforced with fines, is coupled with subsidized tractors. To evaluate this policy, a discrete choice experiment and contingent valuation were merged into a novel statistical variant of the Hicks-Kaldor test that is robust to preference heterogeneity. Among 27 ways to extend the ban, 5 could improve both respiratory health and smallholders’ welfare, when compensated with tractors that are available for longer hours and at the right time of the year. (JEL Q51, Q52)